Fast Three‐Dimensional Search Algorithm to Improve the Carrier Tracking Performance During the Entry, Descent, and Landing (EDL) Phase of Mars Probes - Deng, Tao; Ma, Maoli; Liu, Qinghui (Radio science, 2023)
Carrier tracking for highly dynamic and extremely weak signals is challenging, including during the entry, descent, and landing phase of Mars rovers and the soft landing of lunar probes. In this study, a novel frequency detector is designed based on the frequency maximum likelihood estimator, and a frequency‐locked loop algorithm is constructed. The frequency‐locked loop is suitable for tracking Doppler shifts with large first and second derivatives. Compared with the Jet Propulsion Laboratory frequency maximum likelihood estimator, the computation time is significantly reduced. The simulation results illustrate the effectiveness of the proposed algorithm. This method provides a good method for Doppler frequency measurement in deep space exploration, especially when tracking highly dynamic and extremely weak signals. Key Points Carrier tracking during the entry, descent, and landing phase of Mars rovers in deep space exploration is challenging A fast three‐dimensional search algorithm is proposed Compared with the Jet Propulsion Laboratory three‐dimensional search algorithm, the new algorithm greatly reduces the amount of computation